# Apply the distributive law to the expansion of algebraic expressions, including binomials, and collect like terms where appropriate (VCMNA306)

[/fusion_text][fusion_text]LO: To use the distributive law to expand expressions and collect like terms.
Know:

• What the distributive law is
• How to expand expressions using the distributive law
• What are like terms
• What are unlike terms
• How to collect like terms to simplify expressions

Understand:

• That the distributive law can be used to expand expressions and that like terms can be collected to simplify expressions.

Do:

• I can use the distributive law to expand expressions and collect like terms.

[/fusion_text][/fullwidth][one_full last=”yes” spacing=”yes” center_content=”no” hide_on_mobile=”no” background_color=”” background_image=”” background_repeat=”no-repeat” background_position=”left top” border_position=”all” border_size=”0px” border_color=”” border_style=”” padding=”” margin_top=”” margin_bottom=”” animation_type=”” animation_direction=”” animation_speed=”0.1″ class=”” id=””][fusion_text]

# Distributive Law

[/fusion_text][/one_full][one_half last=”no” spacing=”yes” center_content=”no” hide_on_mobile=”no” background_color=”” background_image=”” background_repeat=”no-repeat” background_position=”left top” border_position=”all” border_size=”0px” border_color=”” border_style=”” padding=”” margin_top=”” margin_bottom=”” animation_type=”” animation_direction=”” animation_speed=”0.1″ class=”” id=””][fusion_text]

### In this case, the coefficient is k and I’m going to multiply it by “a” and “b”, which gives me a new expression of ka + kb.

[/fusion_text][imageframe lightbox=”no” lightbox_image=”” style_type=”none” hover_type=”none” bordercolor=”” bordersize=”0px” borderradius=”0″ stylecolor=”” align=”none” link=”” linktarget=”_self” animation_type=”0″ animation_direction=”down” animation_speed=”0.1″ hide_on_mobile=”no” class=”” id=””] [/imageframe][/one_half][one_half last=”yes” spacing=”yes” center_content=”no” hide_on_mobile=”no” background_color=”” background_image=”” background_repeat=”no-repeat” background_position=”left top” border_position=”all” border_size=”0px” border_color=”” border_style=”” padding=”” margin_top=”” margin_bottom=”” animation_type=”” animation_direction=”” animation_speed=”0.1″ class=”” id=””][imageframe lightbox=”no” lightbox_image=”” style_type=”none” hover_type=”none” bordercolor=”” bordersize=”0px” borderradius=”0″ stylecolor=”” align=”none” link=”” linktarget=”_self” animation_type=”0″ animation_direction=”down” animation_speed=”0.1″ hide_on_mobile=”no” class=”” id=””] [/imageframe][fusion_text]

### Since we know that 3k and 2k are like terms, we can simplify it by collecting like terms, which simplifies the expression to k^2 +5k +6.

[/fusion_text][/one_half][one_half last=”yes” spacing=”yes” center_content=”no” hide_on_mobile=”no” background_color=”” background_image=”” background_repeat=”no-repeat” background_position=”left top” border_position=”all” border_size=”0px” border_color=”” border_style=”” padding=”” margin_top=”” margin_bottom=”” animation_type=”” animation_direction=”” animation_speed=”0.1″ class=”” id=””][imageframe lightbox=”no” lightbox_image=”” style_type=”none” hover_type=”none” bordercolor=”” bordersize=”0px” borderradius=”0″ stylecolor=”” align=”none” link=”” linktarget=”_self” animation_type=”0″ animation_direction=”down” animation_speed=”0.1″ hide_on_mobile=”no” class=”” id=””] [/imageframe][fusion_text]

# Student Generated Videos

[/fusion_text][one_half last=”yes” spacing=”yes” center_content=”no” hide_on_mobile=”no” background_color=”” background_image=”” background_repeat=”no-repeat” background_position=”left top” border_position=”all” border_size=”0px” border_color=”” border_style=”” padding=”” margin_top=”” margin_bottom=”” animation_type=”” animation_direction=”” animation_speed=”0.1″ class=”” id=””][youtube id=”https://www.youtube.com/watch?v=Ocj4-Yi5kA0″ width=”600″ height=”350″ autoplay=”no” api_params=”” class=””][/youtube][/one_half][/fullwidth][fullwidth background_color=”” background_image=”” background_parallax=”none” enable_mobile=”no” parallax_speed=”0.3″ background_repeat=”no-repeat” background_position=”left top” video_url=”” video_aspect_ratio=”16:9″ video_webm=”” video_mp4=”” video_ogv=”” video_preview_image=”” overlay_color=”” overlay_opacity=”0.5″ video_mute=”yes” video_loop=”yes” fade=”no” border_size=”0px” border_color=”” border_style=”” padding_top=”20″ padding_bottom=”20″ padding_left=”0″ padding_right=”0″ hundred_percent=”no” equal_height_columns=”no” hide_on_mobile=”no” menu_anchor=”” class=”” id=””][fusion_text]

# Textbook Questions

[/fusion_text][fusion_text]

### Ex 2C pg. 67 Q. 1-4

[/fusion_text][/fullwidth][fullwidth background_color=”” background_image=”” background_parallax=”none” enable_mobile=”no” parallax_speed=”0.3″ background_repeat=”no-repeat” background_position=”left top” video_url=”” video_aspect_ratio=”16:9″ video_webm=”” video_mp4=”” video_ogv=”” video_preview_image=”” overlay_color=”” overlay_opacity=”0.5″ video_mute=”yes” video_loop=”yes” fade=”no” border_size=”0px” border_color=”” border_style=”” padding_top=”20″ padding_bottom=”20″ padding_left=”0″ padding_right=”0″ hundred_percent=”no” equal_height_columns=”no” hide_on_mobile=”no” menu_anchor=”” class=”” id=””][imageframe lightbox=”no” lightbox_image=”” style_type=”none” hover_type=”none” bordercolor=”” bordersize=”0px” borderradius=”0″ stylecolor=”” align=”none” link=”http://www.alamandamaths.com/factorising-algebraic-expressions-by-taking-out-common-algebraic-factors-10/” linktarget=”_self” animation_type=”0″ animation_direction=”down” animation_speed=”0.1″ hide_on_mobile=”no” class=”” id=””] [/imageframe][/fullwidth]